Leslie A. Thompson, A Manual or Digest of the Statute Law of the State of Florida, of a General and Public Character, in Force at the End of the Second Session of the General Assembly of the State, on the Sixth Day of January, 1847, at 547 - (:unkn) unknown (My University, 1847)
Prohibited any male "Indian" from leaving the reservations. Allowed the confiscation of any guns in possession of violators. Violators also subject up to thirty-nine stripes from a whip at the discretion of the Justice.
Keywords: POSSESSION - DANGEROUS PERSONS